Resiliensi Pelajar Madrasah di Era Disrupsi: Praksis Pendidikan Life Skill Melalui Gerakan Sosial IPNU-IPPNU Kediri - Abii Yazid Ngasimul Istadzi; Moch. Mukhlison (Yayasan Pondok Pesantren Sunan Bonang Tuban, 2026)
The era of disruption exposes madrasah students to a multifaceted vulnerability comprising identity crises, mental exhaustion, and exposure to disinformation which frequently eludes the intervention of formal educational curricula. This study aims to deconstruct the life skills education praxis initiated by the Branch Executive Board of the Nahdlatul Ulama Student Association and the Nahdlatul Ulama Female Student Association (PC IPNU-IPPNU) of Kediri Regency, acting as a social movement entity. Employing a qualitative approach with a field case study design, primary data were gathered through in-depth interviews, participant observation, and critical analysis of the organization's operational and administrative documents. The findings reveal three primary outcomes: (1) The organization mobilizes regional-scale social capital through structural penetration across 26 sub-districts and the integration of commissariat boards within formal madrasahs to establish a social safety net; (2) The hidden curriculum is operationalized through the rationalization of work programs across 11 departments and institutions, functioning as an engine for life skills transformation; (3) This praxis constructs student resilience through four comprehensive pillars: personal skills, social skills, academic skills, and vocational skills. This study offers a theoretical novelty, asserting that the resilience of madrasah students is empirically shaped through the dialectics of youth movements, which functionally bridge the gaps left by formal curricular education.